The formation of Kazakhstan’s strategy of the International Development Assistance - Sagidan, Анар Жарылкасынкызы; Karibayeva, Эльмира Толегеновна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
This article considers the problem of Kazakhstan's strategy of the International Development Assistance